Pharmacogenetic predictors of toxicity to platinum based chemotherapy in non-small cell lung cancer patients. (September 2016) - Pérez-Ramírez, Cristina; Cañadas-Garre, Marisa; Alnatsha, Ahmed; Villar, Eduardo; Delgado, Juan Ramón; Faus-Dáder, María José; Calleja-Hernández, Miguel ÿngel
Graphical abstract: Abstract: Platinum-based chemotherapy is the standard treatment for NSCLC patients with EGFR wild-type, and as alternative to failure to EGFR inhibitors. However, this treatment is aggressive and most patients experience grade 3⿿4 toxicities. ERCC1, ERCC2, ERCC5, XRCC1, MDM2, ABCB1, MTHFR, MTR, SLC19A1, IL6 and IL16 gene polymorphisms may contribute to individual variation in toxicity to chemotherapy. The aim of this study was to evaluate the effect of these polymorphisms on platinum-based chemotherapy in NSCLC patients. A prospective cohorts study was conducted, including 141 NSCLC patients. Polymorphisms were analyzed by PCR Real-Time with Taqman ® probes and sequencing. Patients with ERCC1 C118T-T allele (p = 0.00345; RR = 26.05; CI95% = 4.33, 515.77) and ERCC2 rs50872-CC genotype (p = 0.00291; RR = 4.06; CI95% = 1.66, 10.65) had higher risk of general toxicity for platinum-based chemotherapy. ERCC2 Asp312Asn G-alelle, ABCB1 C1236T-TT and the IL1B rs12621220-CT/TT genotypes conferred a higher risk to present multiple adverse events. The subtype toxicity analysis also revealed that ERCC2 rs50872-CC genotype (p = 0.01562; OR = 3.23; CI95% = 1.29, 8.82) and IL16 rs7170924-T allele (p = 0.01007; OR = 3.19; CI95% = 1.35, 7.97) were associated with grade 3⿿4 hematological toxicity. We did not found the influence of ERCC1 C8092A, ERCC2 Lys751Gln, ERCC2 Asp312Asn, ERCC5 Asp1104His, XRCC1 Arg194Trp, MDM2 rs1690924, ABCB1 C3435T, ABCB1 Ala893Ser/Thr, MTHFR A1298C, MTHFR C677T, IL1B rs1143623, IL1B rs16944, and IL1B rs1143627 on platinum-based chemotherapy toxicity. In conclusion, ERCC1 C118T, ERCC2 rs50872, ERCC2 Asp312Asn, ABCB1 C1236T, IL1B rs12621220 and IL16 rs7170924 polymorphisms may substantially act as prognostic factors in NSCLC patients treated with platinum-based chemotherapy.